Effect of UV-Light Illumination on Room Temperature ZnO Nanotubes for Ethanol Gas Sensing (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
A gas sensor based on force spun ZnO nanotubes was successfully developed by using a simple and cost-effective approach, as confirmed by SEM, EDS, TGA-DTG and XRD characterization techniques. In order to optimize the sensing performance of the device in terms of sensing response kinetics and stability, the sensor response behavior against ethanol vapor was investigated under dark and UV light. Different reported studies have demonstrated that the resistance of ZnO gas sensors towards ethanol decreases when it is exposed to UV light. In this work, the UV light illumination of the sensor at 370 nm, allowed effectively to activate the detection of ethanol at the ppm level at room-temperature, in contrast to dark conditions. Unexpectedly, it was observed that the resistance behavior of the prepared ZnO sensor was reversed under continuous UV irradiation. The sensing mechanism behind this change is being also discussed.
Keywords: Forcespinning; ZnO; Nanotubes; Ethanol; Gas sensor; UV-light activation; Room temperature